Pengaruh Budaya Kerja Dan Kompetensi Terhadap Kinerja Karyawan Pada Firma NISD & Rekan Jakarta Selatan - Tri Yunianingsih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Employee performance measures the success of an organization in achieving its mission and completing a task. The work culture must be designed in such a way that it achieves the goals of the organization and at the same time realizes the individual goals of employees. Competence can affect the improvement of the performance of an employee when the employee has good competence in a professional attitude such as having a cooperative relationship with a colleague in completing a job. The research method used in this research is statistical quantitative. The population in this study is the entire employee of NISD & Partners with a total population of 36 employees. The data collection technique used is a survey method by spreading the questionnaire. The research uses data analysis methods such as validity test, reliability test, classical assumption test, double linear regression test and hypothesis test. Data analysis uses the IMB program SPSS Statistic Ver. 25. The results of this study show that work culture variables have a positive and significant influence on employee performance.